KULINER SEBAGAI REPRESENTASI IDENTITAS DIASPORA KOREA DI AMERIKA SERIKAT: STUDI KASUS JURU MASAK EDWARD LEE - Radianti, Jasmine Anindita; Zaini, Zaini (Multikultura, 2025)
In recent years, the popularity of Korean cuisine has experienced a significant increase, in parallel with the growing influence of the Korean Wave (hallyu) across various countries. Beyond this cultural phenomenon, Korean diaspora communities have also played a crucial role in promoting Korean cuisine on a global scale. This study aims to analyze the representation of Korean-American diaspora identity through a case study of culinary presentation innovations by chef Edward Lee in the reality show Culinary Class Wars. The research adopts a descriptive qualitative method. The findings indicate that Edward Lee’s diasporic identity is represented through the fusion cuisine he presents, as reflected in his choice of ingredients, presentation style, and the personal narratives that accompany his dishes. Lee embraces both cultural backgrounds and incorporates them as integral components of his identity. This representation also serves as part of the broader strategy of Korean cultural globalization, utilizing global media platforms such as Netflix to convey Korean culture to a worldwide audience through the figure of the diaspora.